2010
DOI: 10.1007/s10612-010-9108-6
|View full text |Cite
|
Sign up to set email alerts
|

Family Leave and Law Enforcement: A Survey of Parents in U.S. Police Departments

Abstract: The women of United States police departments challenge traditional gender role expectations by exhibiting equal competence in a job with a masculine identity. Women also modify police culture in a myriad of ways, one of which is through the special work-related needs that accompany motherhood. Results from a survey of police officers suggest that gendered perceptions regarding work and family persist indicating that a value shift within police departments has occurred. Findings derived from qualitative respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…Dans ce type d'horaire, la question de la garde des enfants est un enjeu pouvant devenir un véritable casse-tête pour les couples policiers (Diotte 2001) 5 . Dans la plupart des cas, les couples policiers dépendent de l'ouverture du supérieur, cette personne décidant de tenir compte, ou non, de leur situation dans l'élaboration des horaires (Schulze 2011;Diotte 2001). Toutefois, si les horaires atypiques peuvent être source de stress, ils sont aussi considérés, dans certains contextes, comme un élément facilitant la conciliation travail-famille.…”
Section: Michèle Diotteunclassified
See 1 more Smart Citation
“…Dans ce type d'horaire, la question de la garde des enfants est un enjeu pouvant devenir un véritable casse-tête pour les couples policiers (Diotte 2001) 5 . Dans la plupart des cas, les couples policiers dépendent de l'ouverture du supérieur, cette personne décidant de tenir compte, ou non, de leur situation dans l'élaboration des horaires (Schulze 2011;Diotte 2001). Toutefois, si les horaires atypiques peuvent être source de stress, ils sont aussi considérés, dans certains contextes, comme un élément facilitant la conciliation travail-famille.…”
Section: Michèle Diotteunclassified
“…Bien qu'une très grande proportion de policiers soient également parents (Duxbury et Higgins 2012), les policières semblent, encore de nos jours, être celles qui portent plus souvent la responsabilité familiale et qui assument une grande partie du travail domestique Tremblay et Lazzari Dodeler 2000). Également, la situation familiale dans laquelle se trouvent beaucoup plus de policiers que de policières, où la prise en charge des enfants est principalement assumée par la conjointe ou le conjoint, peut contribuer à nourrir l'idée que les enjeux liés à la conciliation travail-famille concerne davantage les femmes (Duxbury et Higgins 2012;Schulze 2011). En d'autres mots, la reconnaissance et les accommodements en rapport avec la famille paraissent jouer différemment selon le sexe sur la perception de l'engagement au sein de la profession (Charlesworth, Keen et Whittenbury 2009).…”
Section: Michèle Diotteunclassified
“…Within these modern frameworks, recent research shows how the overt practices of sexual harassment and violence have been replaced with less overt practices, such as the social exclusion of women from informal access to power structures and decision making within the organization, the gendering of the division of labor which results in the marginalization of offenses that disproportionately affect women such as those related to the processing of sexual assault and domestic violence cases (Garcia, 2003; Jordan, 2002; Miller, 1999; Padavic & Reskin, 2002; Rabe-Hemp, 2018; Shelley, Morabito, & Tobin-Gurley, 2011), and policies intended to make the workplace equal, such as light duty policies, haircut policies, and the emphasis on physical strength, all which devalue and fail to accommodate the female body (Kringen & Novich, 2017; Rabe-Hemp & Humiston-Sears, 2015; Schulze, 2010).…”
mentioning
confidence: 99%
“…If all interested women were hired onto police departments without question, the current environment of the police departments and the perception of police work would likely deter many other women considering policing as a profession. Problems such as sexism, harassment, double standards and paternalism cause stress, lack of job satisfaction and even resignations (Martin, 1979;Martin, 1980;Remmington, 1981;Wexler, 1985;Zimmer, 1988;Martin, 1990;Yoder, 1991;Belknap & Shelley, 1992;Martin, 1994;Haarr, 1997a;Haarr, 1997b;Sass & Troyer, 1999;Whetstone & Wilson, 1999;Whetstone, 2001;Krimmel & Gormley, 2003;Haarr, 2005;Lonsway, 2006;Archbold & Schulz, 2008;Bochantin & Cowan, 2008;Gustafson, 2008;Rabe-Hemp, 2008;Wertsch, 2008;Archbold & Hassel, 2009;Cowan & Bochantin, 2009;Rabe-Hemp, 2009;Schulze, 2010a;Schulze, 2010b;Hassell, Archbold, & Stichman, 2011;Haarr &Morash, 2013;Kingshott, 2013). Historically the role of women in policing was not created on an equal footing, with women's work supplementing male police officers and keeping women out of leadership and coveted positions such as detectives (Higgens, 1950;Melchionne, 1967;Remmington, 1981;Martin, 1990;Schulz, 1993a;Schulz, 1993b;…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…An involved spouse can able to help as much as possible by supporting the pregnant woman and newborn child, but a women alone experiences the physical and emotional changes of being pregnant. Also, Schulze (2010a) found that many female police officers perceived inequality in marriages which could force female police officers to take more leave due to childcare as they receive less support at home. Many women keep very active up until their due date, but the manner in which a police department helps or hinders a female police officer determines how well an officer can do their job before and after giving birth.…”
Section: Integration and Socialization Into Policingmentioning
confidence: 99%